2020
DOI: 10.1136/bmjopen-2020-037136
|View full text |Cite
|
Sign up to set email alerts
|

Exploring maintenance of physical activity behaviour change among people living with and beyond gastrointestinal cancer: a cross-sectional qualitative study and typology

Abstract: ObjectivesIn the last decade, there has been a rapid expansion of physical activity (PA) promotion programmes and interventions targeting people living with and beyond cancer (LWBC). The impact that these initiatives have on long-term maintenance of PA remains under-researched. This study sought to explore the experiences of participants in order to characterise those who have and have not successfully sustained increases in PA following participation in a PA intervention after a diagnosis of gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…In depth analysis of the barriers and facilitators to physical activity reported by participants during the pilot study will also help the inform future intervention development decisions, and guide potential changes to the environment and services. Future design considerations for CanMOVE will include when to time the intervention, which outcome measures to use, how to engage the multi-disciplinary team, and how changes of behavior changes may be maintained over the entire length of acute treatment and into survivorship ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…In depth analysis of the barriers and facilitators to physical activity reported by participants during the pilot study will also help the inform future intervention development decisions, and guide potential changes to the environment and services. Future design considerations for CanMOVE will include when to time the intervention, which outcome measures to use, how to engage the multi-disciplinary team, and how changes of behavior changes may be maintained over the entire length of acute treatment and into survivorship ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the challenges of scaling and sustaining PA maintenance interventions and addressing PA barriers, technology-based tools are being explored to support PA maintenance [ 9 , 10 , 11 , 12 ]. The key advantages of technology-supported interventions include their suitability for low-cost remote delivery, increasing reach and scale-up potential, and unique features such as enhanced self-monitoring and feedback on behavior, which can support PA maintenance in oncology [ 13 , 14 , 15 , 16 , 17 ]. The use of technology to support PA maintenance is particularly relevant for rural and remote cancer populations, who have greater PA barriers and more limited access to local PA resources compared to those in urban areas [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous digital PA interventions have shown potential among YACS, but most studies are limited by small sample sizes and short duration (8–12 weeks) 12,13 . For cancer survivors to experience the benefits of PA interventions, sustained adherence is needed; 14 yet, they face challenges engaging in and maintaining PA after treatment 14–16 . Few randomized trials of PA behavior change interventions among cancer survivors report long‐term outcomes at 12 months or beyond, 17–20 and previous systematic reviews have identified the need for more studies to evaluate longer‐term PA behavior change and maintenance of PA outcomes following interventions among cancer survivors 19,21–24 .…”
Section: Introductionmentioning
confidence: 99%